Teori Pembelajaran Islami: Pandangan Al-Ghazali - Milawati (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
This research examines Al-Ghazali's views regarding Islamic learning theory and its application in modern education. Al-Ghazali, an 11th century Muslim scholar and philosopher, emphasized the importance of integrating intellectual and spiritual knowledge in the learning process. This study analyzes the principles of education and learning proposed by Al-Ghazali through his main works, such as "Ihya Ulumuddin" and "Mizan al-'Amal". The research results show that Al-Ghazali prioritizes character and moral education, as well as effective interactive learning methods. This method includes multi-sensory use, project-based learning, and spiritual reflection. Although there are challenges in implementation, such as cultural adaptation and teacher training, the impact on character development and student learning motivation is very significant. This research concludes that Al-Ghazali's learning theory offers a holistic and inclusive approach that is relevant for modern education systems. Implementation of these principles helps prepare students not only for academic success but also for a life of morality and noble character. In addition, this research provides recommendations for the integration of Islamic values ​​in the education curriculum and the development of learning methods that are more relevant to the demands of the times.